Synthesis of chlorophyll thin film from euphoria malaiense leaves by using dip coating sol-gel process - Rizwan Husri Bin Roslan (School of Metallurgy Engineering, University Malaysia Perlis, 2016)
Chlorophyll is the green pigment responsible for the photosynthesis processes that occur in green leaf. The main function of the chlorophyll is to extract sunlight. This function is so desirable in solar cell, as to increase the efficiency of the light to electricity energy conversion. Nowadays, solar cell has the highest energy conversion is up to 33%. The chlorophyll pigment can be extract from green leaf using simple solvent solution. The method is straightforward but the extracted chlorophyll solution is good quality and in decent concentration. Dip coating is a good and easy method to produce a thin layer of chlorophyll film onto a glass slide. Thickness of the chlorophyll thin film were manipulated by arranging equal time of dipping for every substrate. The chlorophyll thin film were analyse using SEM/EDX, XRD and UV-Vis examination to characterize their properties. The surface morphology shows that the grains are very low in numbers and the shapes are not the same. The UV-Vis analysis revealed that the extracted chlorophyll had three absorbance spectra at 205 nm, 265 nm and 670 nm. This show that the extracted chlorophyll contain both chlorophyll-a and chlorophyll-bin the mixture.